HOAX BEHIND STATEMENTS SPOKEN BY THE INDONESIA’S PRESIDENTIAL CANDIDATES OF 2019 ON THE SECOND DEBATE USING THE PROPOSITIONAL MEANING - Anisa Ernatri Hamnasthia; Merry Rullyanti (Literary Criticism, 2020)
This study aims to describe the hoax statements from 2019 Indonesia‟s presidentialcandidate in debate using propositional meaning. The purpose of this study were : 1) Toinvestigate the statements which have indication of hoax. 2) To describe propositionalmeaning behind the statements by presidential candidate in debate. 3) To find out theinfluential factors that make hoax spread. The data were collected through the conversationfrom the 2019 Indonesia‟s presidential candidate debate and analyzed using domain andtaxonomy analysis. The researcher findings showed that 1) There are seven indicated hoaxstatements (9,8%) 2) There are 97,26% statements which have propositional meaning. 3) Themost frequently factor that make hoax spread is factor A (social identity).Keywords: Propositional Meaning, Statements, Presidential Candidates